Survey of Smart Data Acquisition System in Wind Turbine Machines Using Labview and IoT - D, Visali; K, Muthulakshmi (International Journal of Computer Sciences and Engineering, 2019)
The embedded cum LabVIEW technology is now its prime and wealth of knowledge. Embedded technology plays a important role in integrating the various functions associated with it. This needs to tie up the various sources of the department in a closed loop system. This proposed system reduces man power, it also save time and operates efficiently without human interference. This project gives forth to first step for achieving the desired target. I have implemented Report generation & IoT unit for the wind turbine based industry for continuously acquiring the data and implementing the cryptography algorithm in it for security reasons.